An incidental case of successful pregnancy outcome and uneventful vaginal hysterectomy with pelvic floor repair in uterus didelphys unicollis at a remote place: A case report (Indian Journal of Case Reports, 2018)
Congenital malformations in a female genital tract are most commonly diagnosed in the reproductive period. Uterus didelphys, also known as a duplicated uterus, is an embryological abnormality, resulting from a complete failure of fusion of Mullerian ducts causing full uterine development to erroneously occur bilaterally. It is associated with many obstetrical complications and thus has clinical importance. Here, we present the case of an elderly patient with a history of third-degree uterovaginal prolapse with cystocele and rectocele at a remote place. During her reproductive life, she carried her pregnancies to term and delivered by full-term vaginal normal deliveries without any complications. An uncomplicated vaginal hysterectomy with pelvic floor repair was done, and the post-operative period was uneventful.